2020
DOI: 10.1002/jlb.4ab0420-694r
|View full text |Cite
|
Sign up to set email alerts
|

PB1-F2 protein of highly pathogenic influenza A (H7N9) virus selectively suppresses RNA-induced NLRP3 inflammasome activation through inhibition of MAVS-NLRP3 interaction

Abstract: Infection with seasonal as well as highly pathogenic avian influenza A virus (IAV) causes significant morbidity and mortality worldwide. As a major virulence factor, PB1-F2 protein of IAV affects the severity of disease through multiple mechanisms including perturbation of host innate immune response. Macrophages are known to phagocytose extracellular PB1-F2 protein aggregate, leading to hyperactivation of NLRP3 inflammasome and excessive production of IL-1 and IL-18. On the other hand, when expressed intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Interestingly, instead of activating NLRP3 inflammasome maturation, intracellularly expressed PB1‐F2 seems to suppress NLRP3 inflammasome activation as demonstrated in NLRP3 inflammasome reconstitution experiment in nonphagocytic cell line HEK293T 41 . We have recently found that intracellular PB1‐F2 suppresses inflammasome in an IAV subtype‐dependent manner, with PB1‐F2 of highly pathogenic IAV being a less potent suppressor than PB1‐F2 of low pathogenicity IAV 66 . This suggests that the ability to activate NLRP3 inflammasome is specific to extracellular PB1‐F2.…”
Section: Extracellular Pb1‐f2—nlrp3 Inflammasome Activation and Necrosismentioning
confidence: 95%
“…Interestingly, instead of activating NLRP3 inflammasome maturation, intracellularly expressed PB1‐F2 seems to suppress NLRP3 inflammasome activation as demonstrated in NLRP3 inflammasome reconstitution experiment in nonphagocytic cell line HEK293T 41 . We have recently found that intracellular PB1‐F2 suppresses inflammasome in an IAV subtype‐dependent manner, with PB1‐F2 of highly pathogenic IAV being a less potent suppressor than PB1‐F2 of low pathogenicity IAV 66 . This suggests that the ability to activate NLRP3 inflammasome is specific to extracellular PB1‐F2.…”
Section: Extracellular Pb1‐f2—nlrp3 Inflammasome Activation and Necrosismentioning
confidence: 95%
“…156 Again, PB1-F2 protein of highly pathogenic influenza A (H7N9) seized the IL-1β secretion from IAV-infected macrophages resulting the inhibition of RNA-induced NLRP3 inflammasome activation. 157 However, this protein is the subject of debate concerning its pro-inflammatory properties. Another study has shown that extracellular protein aggregate PB1-F2 phagocytose is known for its macrophages contributing 158 It is still unknown how extracellular and intracellular fabricate PB1-F2 contributes to viral pathogenesis.…”
Section: Rna Viruses That Inhibit Nlrp3 Inflammasomes Using Virus-encoded Proteinsmentioning
confidence: 99%
“…Another study has shown that extracellular protein aggregate PB1-F2 phagocytose is known for its macrophages contributing 158 It is still unknown how extracellular and intracellular fabricate PB1-F2 contributes to viral pathogenesis. 157 PYD-containing viral proteins, such as the Shope fibroma virus (SFV)-encoded PYD-only protein/macromolecule (vPOP) and the M13L protein of poxvirus, co-localize and associate with ASC via PYD-PYD interactions and then prevent caspase-1 activation and IL-1β production. 159,160 The NS1 protein of influenza A virus can inhibit the NLRP3 inflammasome, 161 with NS1 proteins from both extremely infective and low-pathogenicity strains dramatically reducing IL-1β and IL-18 secretion by LPS-and ATP-treated THP-1 cells.…”
Section: Rna Viruses That Inhibit Nlrp3 Inflammasomes Using Virus-encoded Proteinsmentioning
confidence: 99%
“…The study also showed that the reduction of membrane potential not only suppresses RIG-I signaling, but also blocks NLRP3 inflammasome activation by the co-transfection of inflammasome components in HEK293T cells. Another study further showed that the PB1-F2 of IAV H7N9 selectively suppresses dsRNA-induced NLRP3 inflammasome activation by inhibition of MAVS-NLRP3 interaction [ 119 ]. However, whether PB1-F1 inhibits the activation of inflammasome during viral infection is not clear.…”
Section: Pb1-f2mentioning
confidence: 99%